The Ras signaling pathway in Drosophila. - Wassarman, D.A.; Therrien, M.; Rubin, G.M. (Current Opinion in Genetics and Development, 1995)
During Drosophila eye development, a Ras cascade mediates the decision between neuronal and non-neuronal differentiation of the R7 photoreceptor precursor. Recent genetic and molecular studies have identified a set of protein kinases as components of the Ras cascade and nuclear targets of the cascade, including Yan, Pointed, Jun, and Phyllopod. The Ras cascade functions in other Drosophila signal transduction pathways, eliciting a distinct response in each case, presumably through phosphorylation of specific transcription factors.